A method for producing a high-formability 7075 aluminum alloy clad sheet for aircraft

CN120382331BActive Publication Date: 2026-10-09SHANDONG NANSHAN ALUMINUM +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510766522.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2026-10-09
Estimated Expiration
2045-06-10

AI Technical Summary

Technical Problem

但目前国内7075铝合金包覆薄板材料的研制还存在一些技术难点,尤其在成形性能方面,所制备的退火态7075包覆材料在航空ASTM E290标准下进行弯曲时易出现包覆层裂纹,主要是板材包覆层厚度不均匀、板材包覆过渡区域组织内第二相数量多、尺寸大等问题导致

Benefits of technology

[0024] This invention provides a method for preparing high-formability 7075 aluminum alloy clad sheet for aerospace applications. It employs a two-stage homogenization process with controlled cooling rate to achieve uniform ingot microstructure and reduce the volume fraction of the second phase. A combination of spot welding and riveting is used to fix the cladding material to the core material, while simultaneously controlling the roughness of the cladding surface to ensure a large and firm bonding area between the cladding material and the core material, guaranteeing effective hot rolling welding and uniform cladding thickness during rolling. This method solves problems such as cladding layer detachment or uneven mechanical properties caused by the large number and size of the second phase in the cladding transition region, uneven welding at the cladding-welding interface, and uneven cladding layer thickness. The resulting 7075 clad aluminum sheet exhibits excellent formability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120382331B_ABST
    Figure CN120382331B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a high-forming-performance 7075 aluminum alloy clad sheet for aviation, which comprises the following steps: (1) preparing a 7075 aluminum alloy large-size slab through smelting and casting, and performing homogenization treatment; (2) sawing and milling the homogenization-treated 7075 aluminum alloy slab to obtain a slab with a smooth surface and serving as a core material; (3) determining the size specification of a clad material 7072 aluminum alloy, and brushing and grinding the clad surface of the clad material; (4) bonding the clad material and the core material, and fixing the two through a combination of spot welding and riveting to obtain a composite slab; and (5) obtaining a 7075 aluminum-clad sheet through hot rolling, cold rolling and annealing of the composite slab. The 7075 aluminum-clad sheet with high forming performance is prepared through the following steps: obtaining a cast slab with uniform structure through double-stage homogenization, fixing the clad material and the core material through a combination of spot welding and riveting, and controlling the roughness of the clad surface of the clad material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy sheet preparation technology, specifically to a method for preparing a high-formability aerospace-grade 7075 aluminum alloy coated sheet. Background Technology

[0002] 7xxx series aluminum alloys belong to the Al-Zn-Mg-Cu alloy system and are heat-treatable, high-strength aluminum alloys. Due to their high specific strength, high-temperature stability, and good weldability, they are often used as fuselage skin materials in the aerospace field. Among them, 7075 aluminum alloy is widely used. To further improve the performance of 7075 aluminum alloy in the harsh environments of aviation and aerospace, a layer of high-purity 7072 aluminum alloy can be coated on the alloy surface to improve its corrosion resistance. This not only provides physical protection to the alloy matrix but also acts as an anode due to its inherent high electrode potential, providing anodic protection. However, the development of 7075 aluminum alloy coated sheet materials in China still faces some technical challenges, especially in terms of formability. When the annealed 7075 coated material is bent under the aerospace ASTM E290 standard, cracks easily appear in the coating layer. This is mainly due to uneven coating layer thickness and the large number and size of the second phase in the transition region of the coating. Summary of the Invention

[0003] To solve the above-mentioned technical problems, the present invention provides a method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet.

[0004] The technical solution adopted in this invention is as follows:

[0005] A method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet includes the following steps:

[0006] (1) Prepare raw materials according to the composition and proportion of 7075 aluminum alloy, obtain large-sized flat ingots by smelting and casting, and put the flat ingots into a homogenizing furnace for homogenization treatment.

[0007] (2) The 7075 aluminum alloy flat ingots after homogenization treatment are sawed and milled to obtain flat ingots with smooth surfaces and used as core materials.

[0008] (3) Determine the size specifications of the 7072 aluminum alloy cladding material according to the size of the 7075 aluminum alloy flat ingot core material, brush and polish the cladding surface of the cladding material, and then clean and dry the cladding surface of the cladding material.

[0009] (4) The coating material obtained in step (3) is bonded to the core material, and the coating material and the core material are fixed by a combination of spot welding and riveting to obtain a composite flat ingot fixed as one piece.

[0010] (5) The composite flat ingot obtained in step (4) is hot rolled, cold rolled and annealed to obtain 7075 aluminum sheet.

[0011] Further, the alloy composition of the 7075 aluminum alloy in step (1) is as follows: by mass percentage, Si≤0.40%, Fe≤0.50%, Cu:1.2~2.0%, Mn≤0.30%, Mg:2.1~2.9%, Cr:0.18~0.28%, Zn:5.1~6.1%, Ti≤0.20%, other impurity elements, each not exceeding 0.05%, the total not exceeding 0.15%, and the balance being aluminum.

[0012] Furthermore, in step (1), the homogenization process of the flat ingot adopts a two-stage homogenization process, wherein the first-stage homogenization temperature is 465±3℃ and the first-stage homogenization time is 8~10h; the second-stage homogenization temperature is 475±3℃ and the second-stage homogenization time is 25~30h. After the homogenization heat treatment is completed, it is cooled to room temperature at a cooling rate of not less than 60~100℃ / h.

[0013] In the above technical solution, the present invention obtains an ingot with uniform grain structure and reduces the volume fraction of the second phase by performing a two-stage homogenization process on the ingot and controlling the cooling rate.

[0014] Furthermore, in step (2), when sawing the flat ingot, the gate end is sawn by 1.5 to 2.0% and the expansion end is sawn by 4.0 to 5.0%; when milling the flat ingot, the upper and lower surfaces of the flat ingot are milled by 10.0 to 14.0%.

[0015] In the above technical solution, the present invention removes the segregated layer of the ingot by controlling the milling amount, ensuring uniform grain structure in the transition zone between the cladding material and the core material, and improving the welding effect. Due to element diffusion issues, the coarse-grained layer or segregated layer exhibits severe phase coarsening, and contains numerous impurity elements, coarse primary phases, and coarse secondary phases. This can easily lead to microcracks or porosity during the welding process, affecting the welding quality and consequently the formability of the 7075 aluminum alloy clad sheet material.

[0016] Furthermore, the roughness of the coating surface of the coating material after brushing in step (3) is 2.5 to 3.5 μm.

[0017] In the above technical solution, the present invention not only removes the surface oxide layer of the coating material by brushing and grinding the coating surface, but also controls its surface roughness within a certain range, which can increase the contact area between the coating material and the core material and improve the welding performance of the coating material and the core material during hot rolling. However, the roughness of the coating surface should not be too large, otherwise the cleaning agent and other substances on the coating surface will not be completely removed, resulting in defects such as poor welding between the coating material and the core material. In addition, if the roughness of the coating surface is too large, it may also affect the flow performance of the coating material during hot rolling, resulting in uneven coating layer, or even affecting the coating area, resulting in the coating layer not completely covering the core material.

[0018] Furthermore, in step (3), for the finished product being a 7075 clad aluminum sheet with a thickness of 1.60 to 4.75 mm, the nominal cladding rate is set to 3.0%, and the minimum cladding rate is not less than 2.5%; and the thickness of the cladding material is 15 to 25 mm, the width of the cladding material is (effective rolling surface width of the core material - (20 ± 15 mm) × 2), and the length is (core material length - (200 ± 10 mm) × 2).

[0019] Furthermore, in step (4), when the covering material is fixed to the core material, the welding wire and rivet used at the spot welding position and the riveting position are made of the same material as the core material. The spot welding position and the riveting position are set on both sides of the covering material. The spot welding position and the riveting position on each side are evenly distributed alternately. The spot welding position or the riveting position at the very end is 20 to 50 mm away from the end edge of the covering material. The distance between the spot welding position and the riveting position is 200 mm to 600 mm.

[0020] Further, the hot rolling process in step (5) is as follows: the composite ingot is placed in a heating furnace and heated to 415-430℃, held for 2-4 hours and then hot rolled, with 20-25 hot rolling passes; the reduction in the first two passes is 1-4mm, the rolling speed is 0.35-0.5m / s, and the composite flat ingot is welded and rolled; the emulsion spraying is turned on in the third pass, with the upper surface spraying amount being 15-25% and the lower surface spraying amount being 40-55%; in the 10th or 13th pass, the emulsion spraying amount is increased to the upper surface spraying amount being 35-45% and the lower surface spraying amount being 70-80%; from the 4th pass onwards, the reduction in each pass is controlled to be ≤30mm, the rolling speed is controlled to be ≤2.0m / s, the final rolling temperature is controlled to be 300-330℃, and the thickness of the hot-rolled finished product is 5.0-8.0mm.

[0021] Further, the cold rolling process in step (5) specifically involves: cold rolling the hot-rolled finished billet to the target thickness in 2 to 4 passes, ensuring a cold rolling deformation rate of 50 to 80%, and controlling the rolling speed at 0.35 to 0.5 m / s, ultimately obtaining a 7075 aluminum sheet with a thickness of 1.60 to 4.75 mm.

[0022] Furthermore, the annealing process in step (5) is as follows: the annealing temperature is 475±2℃ and the annealing time is 2~3h.

[0023] The beneficial effects of this invention are as follows:

[0024] This invention provides a method for preparing high-formability 7075 aluminum alloy clad sheet for aerospace applications. It employs a two-stage homogenization process with controlled cooling rate to achieve uniform ingot microstructure and reduce the volume fraction of the second phase. A combination of spot welding and riveting is used to fix the cladding material to the core material, while simultaneously controlling the roughness of the cladding surface to ensure a large and firm bonding area between the cladding material and the core material, guaranteeing effective hot rolling welding and uniform cladding thickness during rolling. This method solves problems such as cladding layer detachment or uneven mechanical properties caused by the large number and size of the second phase in the cladding transition region, uneven welding at the cladding-welding interface, and uneven cladding layer thickness. The resulting 7075 clad aluminum sheet exhibits excellent formability. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is a metallographic photograph of the homogenized ingot in Embodiment 2 of the present invention;

[0027] Figure 2 SEM images of the coating layer and transition region of the coated thin plate prepared in Example 2 of the present invention;

[0028] Figure 3 These are photographs of the bending performance test of the coated sheet prepared in Example 2 of the present invention;

[0029] Figure 4 This is a metallographic photograph of the homogenized ingot in Comparative Example 5 of the present invention. Detailed Implementation

[0030] This invention provides a method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0031] Example 1

[0032] This embodiment describes the preparation of a 7075 aluminum alloy coated sheet for aerospace applications. The steps are as follows:

[0033] (1) 7075 aluminum alloy flat ingots are made of large-sized flat ingots with a size of 480mm (thickness) × 2000mm (width) × 6000mm (length). They are produced by semi-continuous casting. The alloy composition is (mass fraction / wt.%) Si: 0.19, Fe: 0.16, Cu: 1.45, Mn: 0.08, Mg: 2.33, Cr: 0.21, Zn: 5.63, Ti: 0.03. After casting, the flat ingots are placed in a homogenizing furnace for a two-stage homogenization treatment of 468℃×10h+478℃×28h. After the homogenization heat treatment is completed, the ingots are cooled to room temperature at a cooling rate of 70℃ / h.

[0034] (2) After homogenization, the gate end of the 7075 aluminum alloy flat ingot is sawn off to remove 150mm of waste ingot and the expansion end is sawn off to remove 300mm of waste ingot. The upper and lower surfaces of the flat ingot are milled to remove 25mm of segregation layer and the side surface of the flat ingot is milled to remove 5mm of segregation layer. A smooth flat ingot with a specification of 430mm (thickness) × 1990mm (width) × 5550mm (length) is obtained as the core material.

[0035] (3) Based on the dimensions of the 7075 aluminum alloy flat ingot core material, determine the dimensions of the 7072 aluminum alloy cladding material. The design cladding rate is 3.0%. The thickness of the 7072 aluminum alloy cladding material is determined to be 23mm, the width to be 1930mm, and the length to be 5130mm. The cladding surface of the cladding material is brushed to remove the surface oxide layer. At the same time, the surface roughness is controlled to be 3.0μm to increase the contact area. After brushing, the cladding surface is cleaned and dried to ensure that the brushing is uniform and without omissions, and that there are no foreign objects such as dust, oil, or aluminum chips.

[0036] (4) The core material is coated with 7072 aluminum alloy after brushing and polishing. The coating material is bonded to the core material and the coating material is fixed to the core material by spot welding and riveting to obtain a composite flat ingot fixed as one piece. Specifically, the welding wire and rivets used for spot welding and riveting are all made of 7075 aluminum alloy. The spot welding position and the riveting position are set on both sides of the coating material. The spot welding position and the riveting position on each side are evenly distributed alternately. The spot welding position or riveting position at the end of each side is 15mm away from the end edge of the coating material. The distance between two adjacent spot welding positions and riveting positions is 300mm.

[0037] (5) The composite flat ingot is placed in a heating furnace for preheating at 420℃ for 2.5h before hot rolling. After heating, hot rolling is carried out with 25 passes. In the first and second passes, the reduction is 3mm and the rolling speed is 0.40m / s. In the third pass, emulsion spraying is turned on, with 20% spraying on the upper surface and 40% spraying on the lower surface. After the fourth pass, the reduction is controlled to be ≤30mm and the rolling speed to be ≤2.0m / s. In the tenth pass, the emulsion spraying amount is increased to 40% of the upper surface spraying amount. The lower surface is sprayed with 70% of the material; the final rolling temperature is controlled at 330℃, and the thickness of the hot-rolled finished product is 7.5mm; then the hot-rolled finished product billet is cold-rolled in two passes to the target thickness of 4.6mm, with a reduction of 1.80mm in the first pass and 1.10mm in the second pass, and the rolling speed is controlled at 0.40m / s, finally obtaining a cold-rolled finished product with a thickness of 4.6mm; then the cold-rolled finished product is continuously annealed in an air-cushion continuous annealing furnace at 475℃ for 2h to obtain a fully recrystallized annealed 7075 aluminum sheet.

[0038] The annealed 7075 aluminum sheet prepared in this embodiment has a uniform cladding thickness and good cladding effect; its tensile strength is 199MPa, yield strength is 100MPa, and elongation is 25%, which meets the standards for 7075 aerospace aluminum; under the condition of a bending indenter radius of 9.5mm, according to the ASTM E290-14 standard test, it bends 180° without cracks.

[0039] Example 2

[0040] This embodiment describes the preparation of a 7075 aluminum alloy coated sheet for aerospace applications. The steps are as follows:

[0041] (1) 7075 aluminum alloy flat ingots are made of large-sized flat ingots with a size of 480mm (thickness) × 2000mm (width) × 6000mm (length). They are produced by semi-continuous casting. The alloy composition is (mass fraction / wt.%) Si: 0.22, Fe: 0.18, Cu: 1.85, Mn: 0.05, Mg: 2.83, Cr: 0.22, Zn: 5.96, Ti: 0.03. After casting, the flat ingots are placed in a homogenizing furnace for a two-stage homogenization treatment of 465℃×9h + 474℃×25h. After the homogenization heat treatment is completed, the ingots are cooled to room temperature at a cooling rate of 90℃ / h.

[0042] (2) After homogenization, the gate end of the 7075 aluminum alloy flat ingot is sawn off to remove 200mm of waste ingot and the expansion end is sawn off to remove 380mm of waste ingot. The upper and lower surfaces of the flat ingot are milled to remove 30mm of segregation layer and the side surface of the flat ingot is milled to remove 8mm of segregation layer. A smooth flat ingot with a specification of 420mm (thickness) × 1984mm (width) × 5420mm (length) is obtained as the core material.

[0043] (3) Based on the dimensions of the 7075 aluminum alloy flat ingot core material, determine the dimensions of the 7072 aluminum alloy cladding material. The design cladding rate is 3.0%. The thickness of the 7072 aluminum alloy cladding material is determined to be 25mm, the width to be 1930mm, and the length to be 5130mm. The cladding surface of the cladding material is brushed to remove the surface oxide layer. At the same time, the surface roughness is controlled to be 2.8μm to increase the contact area. After brushing, the cladding surface is cleaned and dried to ensure that the brushing is uniform and without omissions, and that there are no foreign objects such as dust, oil, or aluminum chips.

[0044] (4) The core material is coated with 7072 aluminum alloy after brushing and polishing. The coating material is attached to the core material and the coating material is fixed to the core material by spot welding and riveting to obtain a composite flat ingot fixed as one piece. Specifically, the welding wire and rivets used for spot welding and riveting are all made of 7075 aluminum alloy. The spot welding position and the riveting position are set on both sides of the coating material. The spot welding position and the riveting position on each side are evenly distributed alternately. The spot welding position or riveting position at the end of each side is 15mm away from the end edge of the coating material. The distance between two adjacent spot welding positions and riveting positions is 510mm.

[0045] (5) The composite flat ingot is placed in a heating furnace for preheating at 430℃ for 2 hours before hot rolling. After heating, hot rolling is carried out with 21 passes. In the first and second passes, the reduction is 4 mm and the rolling speed is 0.40 m / s. In the third pass, emulsion spraying is turned on, with 25% spraying on the upper surface and 50% spraying on the lower surface. After the fourth pass, the reduction is controlled to be ≤30 mm and the rolling speed to be ≤2.0 m / s. In the tenth pass, the emulsion spraying is increased to 45% on the upper surface and 75% on the lower surface. The final rolling temperature is controlled at 320℃, and the thickness of the hot-rolled finished product is 6.5mm. Then, the hot-rolled finished product billet is cold-rolled in 3 passes to the target thickness of 3.25mm, where the reduction in the first pass is 1.25mm, the reduction in the second pass is 0.90mm, and the reduction in the third pass is 1.10mm. The rolling speed is controlled at 0.35m / s, and finally a cold-rolled finished product with a thickness of 3.25mm is obtained. Then, the cold-rolled finished product is continuously annealed in an air-cushion continuous annealing furnace at 477℃ for 2h to obtain a fully recrystallized annealed 7075 aluminum sheet.

[0046] Metallographic analysis was performed on samples of the flat ingots homogenized in step (1) of this embodiment, such as... Figure 1 As shown. From Figure 1 It can be seen that after two-stage homogenization, the ingot structure is uniform and there are no coarse second phases.

[0047] The annealed 7075 aluminum foil prepared in this embodiment was subjected to SEM analysis, such as... Figure 2 As shown. From Figure 2 As can be seen from this, the 7075 aluminum sheet prepared in this embodiment has a uniform cladding thickness, good welding in the transition area between the cladding and the core material, no coarse second phase aggregation, and no defects such as cracks, inclusions, or pores.

[0048] The annealed 7075 clad aluminum sheet prepared in this embodiment was subjected to mechanical property testing. Its tensile strength was 187.5 MPa, yield strength was 92.4 MPa, and elongation was 22.5%, meeting the standards for 7075 aerospace aluminum materials. Furthermore, the cladding layer exhibited uniform coating effect. The annealed 7075 clad aluminum sheet prepared in this embodiment was also subjected to bending performance testing. Bending test photographs are shown below. Figure 3 As shown. From Figure 3 As can be seen from the results, the 7075 aluminum sheet prepared in this embodiment, under the condition of a bending indenter radius of 6.5 mm, showed no cracks when bent 180° according to the ASTM E290-14 standard test.

[0049] Comparative Example 1

[0050] Comparative Example 1 prepares a 7075 aluminum alloy coated sheet for aerospace applications. The difference between this and Example 2 is that the coated surface of the coated material in this comparative example is brushed and polished, and the roughness after brushing and polishing is 6.0 μm.

[0051] The 7075 clad aluminum sheet prepared in this comparative example cracked after bending 180° according to ASTM E290-14 standard test with a bending indenter radius of 6.5 mm. This is because the high roughness of the comparative example resulted in insufficient rolling or uneven rolling deformation due to frictional resistance under normal rolling force, leading to uneven cladding thickness and failure to fully cover the cladding in some width directions.

[0052] Comparative Example 2

[0053] Comparative Example 2 prepares a 7075 aluminum alloy coated sheet for aerospace applications. The difference between this and Example 2 is that the coated surface of the coated material in this comparative example is brushed and polished, and the roughness after brushing and polishing is 1.0 μm.

[0054] The 7075 clad aluminum sheet prepared in this comparative example cracked after bending 180° according to ASTM E290-14 standard test under a bending head radius of 6.5 mm. This is because the roughness of the contact surface between the cladding material and the core material was low during the rolling process in this comparative example, resulting in relatively fast flow of the cladding metal under normal rolling force and low density of the weld interface between the cladding and the core material.

[0055] Comparative Example 3

[0056] Comparative Example 3 prepares a 7075 aluminum alloy clad sheet for aerospace applications. The difference between this comparative example and Example 2 is that this comparative example uses a combination of spot welding and riveting to fix the cladding material and the core material. The spot welding positions are evenly distributed on one side edge of the cladding material, and the riveting positions are evenly distributed on the other side edge of the cladding material.

[0057] The 7075 aluminum sheet prepared in this comparative example fractured after bending 180° under the condition of a bending indenter radius of 6.5 mm, according to the ASTM E290-14 standard test. Furthermore, some welded materials showed cracking during the rolling process due to the different bearing capacity of the welds on both sides, and the crack initiation was more likely to occur on the spot weld side.

[0058] Comparative Example 4

[0059] Comparative Example 4 prepares a 7075 aluminum alloy clad sheet for aviation use. The difference between this and Example 2 is that only riveting is used to fix the cladding material and the core material in this comparative example. The riveting positions are set on both sides of the cladding material and the riveting positions on each side are evenly distributed.

[0060] The 7075 aluminum sheet prepared in this comparative example has a uniform cladding thickness and good welding in the transition area between the cladding and the core material. Furthermore, under a bending head radius of 6.5 mm, it showed no cracks after bending 180° according to ASTM E290-14 standard testing. However, riveting requires secondary processing of both the core material and the cladding material, resulting in a cumbersome production process and high manufacturing costs.

[0061] Comparative Example 5

[0062] Comparative Example 5 prepares a 7075 aluminum alloy coated sheet for aerospace applications. The difference between this and Example 2 is that the homogenization process used for the flat ingot in this comparative example is 460℃×9h, and after homogenization, furnace cooling is performed at a cooling rate of 40℃ / h.

[0063] The 7075 aluminum sheet prepared in this comparative example cracked after bending 180° under a bending indenter radius of 6.5 mm, according to ASTM E290-14 standard testing. The main reason is: (referring to...) Figure 4 The homogenization process used in this comparative example had poor homogenization effect, with a large amount of residual second phase and eutectic structure in the ingot. This resulted in a large amount of coarse phase residue during the subsequent welding and rolling process, which in turn caused poor coating effect of the formed coating layer and cracking during bending.

[0064] Analysis of the test results of the above embodiments and comparative examples reveals the following: Embodiment 2 of the present invention employs a two-stage homogenization process with controlled cooling rate to achieve uniform ingot structure and reduce the volume fraction of the second phase. It also uses a combination of spot welding and riveting to fix the cladding material and core material, while controlling the roughness of the cladding surface to ensure a large and firm bonding area between the cladding material and core material, guaranteeing the hot-rolled welding effect. Furthermore, the uniform thickness of the cladding layer during rolling results in good formability of the prepared 7075 clad aluminum sheet, preventing cracking during bending. Moreover, the combination of spot welding and riveting in Embodiment 2, combined with the appropriate surface roughness, achieves the same effect as the riveting-only fixation method in Comparative Example 4. However, the method in Embodiment 2 reduces the number of riveting positions, decreases the workload of secondary processing, and lowers production costs.

[0065] It should be noted that any parts not mentioned in this invention can be achieved by using or referencing existing technologies.

[0066] Of course, the above description is not intended to limit the present invention, and the present invention is not limited to the examples given above. Any changes, modifications, additions or substitutions made by those skilled in the art within the scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet, characterized in that, Including the following steps: (1) Prepare raw materials according to the composition and proportion of 7075 aluminum alloy, obtain large-sized flat ingots by smelting and casting, and put the flat ingots into a homogenizing furnace for homogenization treatment; (2) The 7075 aluminum alloy flat ingots after homogenization treatment are sawed and milled to obtain flat ingots with smooth surfaces and used as core materials; (3) Determine the size specifications of the 7072 aluminum alloy cladding material according to the size of the 7075 aluminum alloy flat ingot core material, brush and polish the cladding surface of the cladding material, and then clean and dry the cladding surface of the cladding material. (4) The coating material obtained in step (3) is bonded to the core material, and the coating material and the core material are fixed by a combination of spot welding and riveting to obtain a composite flat ingot fixed as one piece. (5) The composite flat ingot obtained in step (4) is hot rolled, cold rolled and annealed to obtain 7075 aluminum sheet; In step (4), when the covering material is fixed to the core material, the welding wire and rivet used at the spot welding position and the riveting position are made of the same material as the core material. The spot welding position and the riveting position are set on both sides of the covering material. The spot welding position and the riveting position on each side are evenly distributed alternately. The spot welding position or the riveting position at the very end is 10~30mm away from the end edge of the covering material. The distance between the spot welding position and the riveting position is 200mm~600mm. The hot rolling process in step (5) is as follows: the composite ingot is placed in a heating furnace and heated to 415~430℃, held for 2~4 hours and then hot rolled, with 20~25 hot rolling passes; the first two passes have a reduction of 1~4mm and a rolling speed of 0.35~0.5m / s for welding and rolling of the composite flat ingot; the third pass starts emulsion spraying, with the upper surface spraying amount of 15~25% and the lower surface spraying amount of 40~55%; in the 10th or 13th pass, the emulsion spraying amount is increased to the upper surface spraying amount of 35~45% and the lower surface spraying amount of 70~80%; from the 4th pass onwards, the reduction of each pass is controlled to ≤30mm, the rolling speed is controlled to ≤2.0m / s, the final rolling temperature is controlled to 300~330℃, and the thickness of the hot rolled finished product is 5.0~8.0mm.

2. The method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet according to claim 1, characterized in that, The alloy composition of the 7075 aluminum alloy in step (1) is as follows: by mass percentage, Si≤0.40%, Fe≤0.50%, Cu:1.2~2.0%, Mn≤0.30%, Mg:2.1~2.9%, Cr:0.18~0.28%, Zn:5.1~6.1%, Ti≤0.20%, and other impurity elements, each not exceeding 0.05%, and the total not exceeding 0.15%, with the balance being aluminum.

3. The method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet according to claim 1, characterized in that, In step (1), the homogenization process of the flat ingot adopts a two-stage homogenization process. The first-stage homogenization temperature is 465±3℃ and the first-stage homogenization time is 8~10h. The second-stage homogenization temperature is 475±3℃ and the second-stage homogenization time is 25~30h. After the homogenization heat treatment is completed, the ingot is cooled to room temperature at a cooling rate of not less than 60~100℃ / h.

4. The method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet according to claim 1, characterized in that, In step (2), when sawing the flat ingot, the gate end is sawn by 1.5~2.0% and the expansion end is sawn by 4.0~5.0%; when milling the flat ingot, the upper and lower surfaces of the flat ingot are milled by 10.0~14.0%.

5. The method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet according to claim 1, characterized in that, The roughness of the coating surface of the coating material after brushing in step (3) is 2.5~3.5μm.

6. The method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet according to claim 1, characterized in that, In step (3), for 7075 aluminum sheet with a thickness of 1.60~4.75mm, the nominal cladding rate is set to 3.0%, and the minimum cladding rate is not less than 2.5%; and the thickness of the cladding material is 15~25mm, the width of the cladding material is (effective rolling surface width of core material - (20±15mm)×2), and the length is (core material length - (200±10mm)×2).

7. The method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet according to claim 1, characterized in that, The cold rolling process in step (5) is as follows: the hot-rolled finished billet is cold-rolled to the target thickness in 2 to 4 passes, ensuring that the cold rolling deformation rate is 50 to 80% and the rolling speed is controlled at 0.35 to 0.5 m / s, and finally a 7075 aluminum sheet with a thickness of 1.60 to 4.75 mm is obtained.

8. The method for preparing a high-formability aerospace-grade 7075 aluminum alloy clad sheet according to claim 1, characterized in that, The annealing process in step (5) is as follows: the annealing temperature is 475±2℃ and the annealing time is 2~3h.

Citation Information

Patent Citations

  • Soldering compounding technology of aluminum alloy for automobile heat exchange system

    CN109016774A

  • Aluminum alloy composite material containing high-proportion return material, and preparation method thereof

    CN111086292A